2012
DOI: 10.1530/joe-12-0131
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular ATP signaling via P2X4 receptor and cAMP/PKA signaling mediate ATP oscillations essential for prechondrogenic condensation

Abstract: Prechondrogenic condensation is the most critical process in skeletal patterning. A previous study demonstrated that ATP oscillations driven by Ca 2C oscillations play a critical role in prechondrogenic condensation by inducing oscillatory secretion. However, it remains unknown what mechanisms initiate the Ca 2C -driven ATP oscillations, mediate the link between Ca 2C and ATP oscillations, and then result in oscillatory secretion in chondrogenesis. This study has shown that extracellular ATP signaling was requ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 51 publications
1
37
0
Order By: Relevance
“…Purinergic receptors are known to mediate Ca 2+ oscillations in various cell types [10,13,22,28]. In this work, we propose that purinergic signalling may be the main drive Ca 2+ of oscillations in CPCs as (1) breakdown of extracellular ATP and ADP by apyrase was able to completely abrogate Ca 2+ oscillations, and (2) the very same P2 purinergic receptors (i.e.…”
Section: Purinergic Signalling In Cpcs and Autocrine/paracrine Regulamentioning
confidence: 88%
“…Purinergic receptors are known to mediate Ca 2+ oscillations in various cell types [10,13,22,28]. In this work, we propose that purinergic signalling may be the main drive Ca 2+ of oscillations in CPCs as (1) breakdown of extracellular ATP and ADP by apyrase was able to completely abrogate Ca 2+ oscillations, and (2) the very same P2 purinergic receptors (i.e.…”
Section: Purinergic Signalling In Cpcs and Autocrine/paracrine Regulamentioning
confidence: 88%
“…In recent years, considerable efforts have been made to discover novel effective antagonists of P2X 4 Rs. Although the benzodiazepine derivative 5-BDBD has been recently proposed to selectively block P2X 4 Rs [27], only limited experiences have been available concerning its inhibitory properties [28,29,30,31]. Moreover, to the best of our knowledge, there are no previous studies attempting to compare the inhibitory effects of 5-BDBD using both electrophysiological and intracellular calcium measurements.…”
Section: Discussionmentioning
confidence: 99%
“…So far, limited experience has been available with 5-BDBD and there is no consensus about its pharmacologically relevant concentration range. In some studies low micromolar (5-10 μM) concentrations were used [28,29] whereas others applied significantly higher doses of 5-BDBD (30-100 μM) [30,31]. …”
Section: Introductionmentioning
confidence: 99%
“…A recent study has also shown that intracellular oscillations in ATP have a critical role in pre-chondrogenic condensation, via P2X4 receptors [321] and mediate inductive action of fibroblast growth factor [322].…”
Section: P2 Receptor Expression By Chondrocytesmentioning
confidence: 98%